2023
DOI: 10.1073/pnas.2310714120
|View full text |Cite
|
Sign up to set email alerts
|

Toward a quantitative interfacial description of solvation for Li metal battery operation under extreme conditions

John Holoubek,
Kunpeng Yu,
Junlin Wu
et al.

Abstract: The future application of Li metal batteries (LMBs) at scale demands electrolytes that endow improved performance under fast-charging and low-temperature operating conditions. Recent works indicate that desolvation kinetics of Li + plays a crucial role in enabling such behavior. However, the modulation of this process has typically been achieved through inducing qualitative degrees of ion pairing into the system. In this work, we find that a more quantitative control of the ion pairing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 64 publications
0
3
0
Order By: Relevance
“…9,16 Few experimental investigations [17][18][19][20][21][22][23][24][25] and computational studies 8,9,26,27 have attempted to obtain an understanding of the Li + ion adsorption process, which includes its dependence on various factors such as the electric double layer (EDL) structure, 16 cation-anion and cation-solvent dissociation energies, 28 and solvation environments. 29 Using AC impedance spectroscopy, Yamada et al 17 showed that the activation energy of the interfacial Li + ion transfer on a highly oriented pyrolytic graphite surface is proportional to the solvation energy of Li + ions, which is a proxy for the energy required for the desolvation of Li + ions from the solvent molecules. In another study, using Raman spectroscopy and AC impedance spectroscopy, Uchida et al 30 reported that increasing the association between Li + ions and anions in the electrolyte reduces the activation energy for Li + ion adsorption from the electrolyte into the graphite.…”
Section: Introductionmentioning
confidence: 99%
“…9,16 Few experimental investigations [17][18][19][20][21][22][23][24][25] and computational studies 8,9,26,27 have attempted to obtain an understanding of the Li + ion adsorption process, which includes its dependence on various factors such as the electric double layer (EDL) structure, 16 cation-anion and cation-solvent dissociation energies, 28 and solvation environments. 29 Using AC impedance spectroscopy, Yamada et al 17 showed that the activation energy of the interfacial Li + ion transfer on a highly oriented pyrolytic graphite surface is proportional to the solvation energy of Li + ions, which is a proxy for the energy required for the desolvation of Li + ions from the solvent molecules. In another study, using Raman spectroscopy and AC impedance spectroscopy, Uchida et al 30 reported that increasing the association between Li + ions and anions in the electrolyte reduces the activation energy for Li + ion adsorption from the electrolyte into the graphite.…”
Section: Introductionmentioning
confidence: 99%
“…On one hand, strong solvation strength of solvent molecules with high donor numbers can facilitate the formation of high-concentration electrolytes (HCEs), thus reducing the free molecules and their side reactions on lithium metal anode . On the other hand, recent efforts have been dedicated to developing weakly solvating electrolytes (WSEs), , which can help create inorganic-rich SEIs on lithium metal anode surfaces that are essential for suppressing Li dendrite growth and improving the cycling performance of LMBs. Although substantial efforts have been dedicated, the progress in developing low-temperature LMBs is still limited due to the lack of suitable electrolytes . Currently, a mechanistic understanding of the intricate interplay between solvation structure and SEI formation is imperative to further improve the performance of low-temperature LMBs.…”
Section: Introductionmentioning
confidence: 99%
“…Few experimental investigations and computational studies ,,, have attempted to obtain an understanding of the Li + ion adsorption process, which includes its dependence on various factors such as the electric double layer (EDL) structure, cation–anion and cation–solvent dissociation energies, and solvation environments . Using AC impedance spectroscopy, Yamada et al showed that the activation energy of the interfacial Li + ion transfer on a highly oriented pyrolytic graphite surface is proportional to the solvation energy of Li + ions, which is a proxy for the energy required for the desolvation of Li + ions from the solvent molecules.…”
Section: Introductionmentioning
confidence: 99%